Altay Türklerinin Geleneksel Aile Yapısı - Kayhan, Shurubu (My University, 2018)
Family institution is the oldest building stone of human history. Despite the changes in the social and human values of the family structure, their basic characteristics are the same. The establishment of the family, the healthy continuation of the establishment, the peace, peace, love and respect concepts of the institution are changing from people to people. Altai family structure has very rich resources in this respect. The forms of marriage that constitute the structure of the family institution should be investigated in terms of marriage age, stages of marriage, family institution, concept of child in family, continuity of family establishment, social, cultural and religious aspects. Altays value is the most important feature of Turkish peoples, which is interesting. It is the living of the beliefs of Christian, Buddha and Shamanism in the same soil. Naturally, these beliefs were also influential on the Altay family structure. I would like to emphasize the traditional family structure of the Altay people, especially the traditions and customs within the family in the family.
Keywords: Evlilik; Aile Kuruluşu; Çoçuklar; Çocuk Yetiştirme; Gelenek ve Görenekler; Marriage; Family Establishment; Children; Child Raising; Traditions and Customs